The Effect of Nitrogen and Potassium Fertilizers and Soil Types on Rubber (Hevea Brasiliensis Muell. Arg.) - Chang, Ah Kaw (1989)
Five fertilizer trials were conducted from 1977 to 1987 to evaluate the effects of different rates of nitrogen (N) and potassium (K) fertilizers on rubber grown on five types of 80ils in Peninsular Malaysia. The treatments consisted of one control (unfertilized ) and nine factorial combinations of nitrogen and potassium fertilizers at three levels each. The levels of fertilizers used were 26.4 kg. 53.3 kg and 79.7 kg N ha-1 yr-1 in combination with 26.0 kg. 60.3 kg and 97.1 kg K ha-1 yr-1 The rubber clone used in these trials was RRIM 600. The five types of soils used were Sitiawan series (Aquoxic Tropudult). Rasau series (Oxic Oystropept). Durian series (Orthox ic Tropudult), Malacca series (Tropeptic Haplorthox) and Munchong series (Tropeptic Haplorthox). Data on growth, yield and leaf nutrient levels were recorded throughout the course of the trials. Soil analyses were undertaken at the beginning and at the end of the trials.